Operational cryopreservation of multi-genera plant genetic resources collections at the National Center for Genetic Resources Preservation - Ellis, D. D; Jenderek, M. M (MTT, 2008)
The U.S. National Center for Genetic Resources Preservation (NCGRP) is focused on research associated with the long-term preservation of plant and animal genetic resources in conjunction with the long-term storage of these resources. The Center securely stores over 730,000 inventories of plant genetic resources, the majority consisting of the base collection for the National Plant Germplasm System (>480,000 inventories). These collections are predominately seed which is dried to between 6% - 10% moisture content and stored at -18oC. However, ~8% of this base collection is stored in the vapour phase of liquid nitrogen. The criteria of which accession to store in liquid nitrogen and which to store conventionally (-18oC) is largely made on a genus-by-genus basis and usually crypreservation is not considered for large sized see and seed with high oil content. Germination of every seed accession which is considered for liquid nitrogen storage is tested both with and without a 24 hour liquid nitrogen exposure to ensure that a particular accession can tolerate liquid nitrogen exposure. In addition to the seed accessions stored at the NPGRP, we also have a large program in the operational storage of vegetatively-propagated accessions in the National Plant Germplasm System. At present, many of these accessions are maintained in a single field site and only ~10% of the 30,000 vegetatively-propagated accessions in the National Plant Germplasm System are backed up in cryopreservation. Due to the very high labour requirements for cryopreserving clonal germplasm collections (20-40 accessions/person/year), the NCGRP has operationally developed a priority system based on existing technology to determine which crops to process for long-term storage. Practically, our efforts are concentrated on crops with developed cryopreservation methods and where support of the crop curator is available. Examples of this collaboration include: 1. Apple (and sour cherry), where a robust dormant bud cryopreservation technology exists. Over 2,500 apple accessions are in cryostorage at NCGRP yet all phases of this work are dependent on the curator doing all grafting to test post-cryo viability as well as carrying out the monitor testing over time. 2. Garlic, where shoot tips are cryopreserved from field grown bulbs. The quantity of bulbs and number of accessions cryopreserved per year is very much dependent on the curator s ability to do the field work. 3. Accessions that require tissue culture plantlets as a source of the shoot tips (mint, strawberry, currents, blackberries, hops, sweet potato, pear). The NCGRP currently does not have the resources to do the isolation and establishment of the shoot cultures and therefore the curator must be willing to do this work in order to have the crop cryopreserved. Operationally, our criteria for having an accession successfully back-up in cryostorage are a minimum of 40% viability in the cryopreserved shoot tips and a minimum 60 viable shoot tips cryostored. For most crops, we store 10 shoot tips/cryo vial and with the criteria for success mentioned above, we have a 99% chance of having at least one viable shoot tip per vial. Fortunately, for the crops we work with, vial-to-vial variability is very low. Research in our operational setting focuses on applying existing techniques to our accessions and laboratory. Often, we need to make minor modifications in techniques so that the techniques are applicable in our system. This research phase may take 1-2 years before we consider a technique for a crop ready to start on a large-scale germplasm preservation project. Banana is a crop in this category in our laboratory where very good existing techniques exist yet it takes time to fully implement them into our operational system. Another area of research in our applied preservation setting is extension of the apple dormant bud cryopreservation system to other woody crops. A major determinant for this research is the relative ease of preserving entire collections if dormant buds can be cryopreserved. This operational research approach was only initiated two years ago but we already have initial success with butternut and preliminary data indicates that material from our warmer-winter sites where vegetatively-propagated material is grown (west coast of the U.S.) can be cryopreserved as well as from colder growing regions. The focus crops for this research include a Prunus program (apricot, almond, peach, sweet cherry and plum), walnut, pear, hazelnut, blueberry, pomegranate and pistachio.
Keywords: Ka